Comparative Study of Indonesia and Denmark in Creating a Smart Environment - Hanif, Nita Aribah; Utomo, Eko Priyono; Husein, Rahmawati (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
This study aims to compare the efforts of the Governments of Indonesia and Denmark in realizing a smart environment SDG's agenda. This urgency is motivated by the poor environmental conditions in Indonesia while the government is targeting a reduction in emission production by 2030. This research uses a qualitative method. The results of this study indicate that the Government of Indonesia in pursuing a smart environment has not been optimal. This can be seen from the several indicators used in this study: (1) the Attraction of Natural Conditions indicator, the Indonesian Government has not enforced regulations or programs aimed at maintaining the balance of green open spaces. Meanwhile, the Danish Government has launched a city greening program through construction of green buildings. (2) Air Pollution Integrated Index indicator, the Indonesian government has not been able to minimize the number of vehicles through the use of electromobility-based vehicles as has been done by the Danish government. (3) Indicators of Sustainable resource management, the Indonesian Government has not been able to optimize the development of technology for processing waste and waste into residues that can be reused. While in Denmark, which is able to turn waste into residue that can be reused.